2023
DOI: 10.1101/2023.01.02.522381
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mechanically induced topological transition of spectrin regulates its distribution in the mammalian cortex

Abstract: The cell cortex is a dynamic assembly formed by the plasma membrane and the underlying cytoskeleton. As the main determinant of cell shape, the cortex ensures its integrity during passive deformation or active response by adapting cytoskeleton topologies with poorly understood mechanisms. The spectrin meshwork ensures such adaptation in erythrocytes and neurons by adopting dramatically different organizations. Erythrocytes rely on triangular-like lattices of spectrin tetramers, which in neurons are organized i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(20 citation statements)
references
References 56 publications
0
20
0
Order By: Relevance
“…We run the simulations in MATLAB R2021a desktop computer. Following (11), for the patch of actin-spectrin meshwork (Figs. [3][4][5][6], we obtain the initial spectrin mesh with the MATLAB's delaunayTriangulation.m function and implement the forward Euler method to solve Eq.…”
Section: Numerical Implementationmentioning
confidence: 99%
See 4 more Smart Citations

Dynamic mechanisms for membrane skeleton transitions

Bonilla-Quintana,
Ghisleni,
Gauthier
et al. 2024
Preprint
Self Cite
“…We run the simulations in MATLAB R2021a desktop computer. Following (11), for the patch of actin-spectrin meshwork (Figs. [3][4][5][6], we obtain the initial spectrin mesh with the MATLAB's delaunayTriangulation.m function and implement the forward Euler method to solve Eq.…”
Section: Numerical Implementationmentioning
confidence: 99%
“…showed that the distribution of spectrin is dynamic and it changes during mechanical challenges like cell adhesion, contraction, compression, stretch, and osmolarity changes ( 10 ). Moreover, recent studies from our group revealed that βII-spectrin transitions between a RBC-like configuration to a periodic axonal configuration in fibroblasts ( 11 ). Such a transition is driven by actomyosin contractility.…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations

Dynamic mechanisms for membrane skeleton transitions

Bonilla-Quintana,
Ghisleni,
Gauthier
et al. 2024
Preprint
Self Cite